Black Fruit Seed Extract Effect on the Memory of Wistar White Mouse Induced Alcl3 - Nurasi Lidya E Marpaung; Abdul Razak; Mayang Sari; Ester Novella Duwit; Febriza Dwi Ranti (Jurnal Health Sains, 2023)
Black fruit seed extract (Haplolobus monticola) contains flavonoid, alkaloid, and terpenoid compounds. Flavonoids are beneficial to the cognitive function of the human brain. Terpenoid derivatives can be used as potential therapeutic agents for the treatment of dementia. Alkaloids have shown good affinity with the cholinergic enzyme AChE. To find out the effect of black fruit seed extract on the memory of Wistar white mouse induced AlCl3. AlCl3 was used to induce experimental animal models of dementia. Experimental design using Complete Randomized Design and is comparative. The subject of the study used was Wistar White Mouse. The subjects of the study were randomly divided into 4 groups including K1 (aquadest 21 days continued Na-CMC 1% 10 days), K2 (AlCl3 21 days followed by Na-CMC 1% 10 days), K3 (AlCl induction 3 21 days continued Donepezil), and K4 (AlCl 3 21 days followed by 10 days). Memory evaluation using Morris water maze test data results were analyzed with a t-test to see differences before treatment and after. Then the One-way Anova test was to see the differences in the results of each group and continued with the Least Significant Difference (LSD) test. The mean value of the morris water maze after therapy administration In the K3 and K4 groups showed significant cognitive improvement. There was no meaningful difference between K3 and K4 against the decrease in the average value of the morris water maze test. Black fruit seed extract can improve memory in a Wistar white mouse that has been induced by AlCl3 and is comparable to donepezil.